Sport Policy in China - Zheng, J.; Chen, S.; Tan, T.-C.; Houlihan, B. (Routledge Research in Sport Politics and Policy, 2018)
Acknowledging China`s established status as a global sporting superpower, this is the first book to systematically investigate sport policy in that country.